Assessments of Heart Rate and Sympathetic and Parasympathetic Nervous Activities of Normal Mouse Fetuses at Different Stages of Fetal Development Using Fetal Electrocardiography - Kasahara, Yoshiyuki; Yoshida, Chihiro; Saito, Masatoshi; Kimura, Yoshitaka (Frontiers in Physiology, 2021)
Heart rate is controlled by the activity of the autonomic nervous system: the sympathetic and parasympathetic nervous systems increase and suppress heart rate, respectively. To evaluate the activity of the autonomic nervous system, it is possible to determine heart rate variability using electrocardiography (ECG). During the fetal period, the heart and autonomic nerves develop in coordination; however, physiological changes, including autonomic nervous activities that occur during the fetal stage, remain largely unknown. Therefore, in this study, we measured ECG signals of mouse fetuses using our established method to evaluate the development of heart rate and autonomic nervous activity at different fetal developmental stages. We found that heart rate was significantly increased in fetal mice at embryonic day (E) 18.5 compared with that at E13.5, E15.5, and E17.5, indicating that fetal heart rate increases only at the stage immediately prior to birth. Interestingly, fetal parasympathetic nervous activity was reduced at E17.5 and E18.5 compared with that at E13.5, whereas fetal sympathetic nervous activity remained unchanged, at least from E13.5 to E18.5. These results indicate that parasympathetic activity rather than sympathetic activity affects fetal heart rate and that the decrease in parasympathetic activity toward the end of pregnancy could result in the observed increase in fetal heart rate.